Obecny stan badań nad Zagładą na Ukrainie - Abakunkova, Anna (Zagłada Żydów. Studia i Materiały, 2014)
The article examines the state of the Holocaust historiography in Ukraine for the period of 2010 – beginning of 2014. The review analyzes activities of major research and educational organizations in Ukraine which have significant part of projects devoted to the Holocaust; main publications and discussions on the Holocaust in Ukraine, including publications of Ukrainian authors in academic European and American journals. The article illustrates contemporary tendencies and conditions of the Holocaust Studies in Ukraine, defines major problems and shows perspectives of the future development of the Holocaust historiography in Ukraine.